Blast test and numerical simulation of point-supported glazing. Issue 12 (December 2016) - Chen, Suwen; Zhu, Chen-Guang; Li, Guo-Qiang; Lu, Yong
The blast resistance of point-supported laminated glass curtain wall has been investigated by means of field blast tests and numerical simulation. Nine site blast tests were carried out, considering two types of glass thickness and six TNT charges ranging from 0.4 to 30 kg. The overpressure and displacement time histories were measured and the failure modes were observed. The overpressure obtained from the measurement panel exhibited a typical pattern of near-field blast with a steep increase followed by a rapid decay within a few milliseconds. The displacement response of the laminated glass panels increased with the increase in the TNT charge almost linearly in the smaller tests (scaled distance ranging 4.5–7 m/kg 1/3 ), which was in line with the increase in the blast impulse in these tests. The failure mode of the point-supported laminated glass panels was featured by tearing off of the polyvinyl butyral layer around the support area, while the glass shards still adhered to the polyvinyl butyral interlayer. Nonlinear dynamic finite element simulation agrees reasonably well with the results from the blast tests. Severe stress concentration has been predicted to occur at the rim of the support holes, leading to initiation of failure at these supports, and this also agrees with the failure mode observed from the blast test. Finally, parametric studies are carried out to investigate the influence of TNT charge weight and the geometric parameters of the panel on the blast response of the glass curtain wall.